Using Determination of ( Fe, Mn, Ni ) in Syrian Costal Sand by BCR sequential extraction method. (Latakia University Journal -Basic Sciences Series, 2018)
Sequential extraction is a useful method of identifying how toxic trace metals bind to sand particles and the strength of these bonds. Sequential extraction uses a series of extractions on the same sample, by using  extraction liquids expected to promote decreasing mobility of metal fractions in  the sand . The selected sequence process named BCR (Community Burean of Reference), is consisting of  four-steps, but with improvements in the fourth step (so it has become two parts ;the first  is: by using the Aqua regia and the second is : by using  Hydrofluoric acid).Seven  different samples of sand  from coastal areas in Syria have been studied. (Fe ,Mn,Ni) have been analyzied and their concentrations have been determined by using Atomic Absorption Spectrometry (AAS),the results have shown that the increasing percentage concentration for  Fe, Mn,Ni in the residual fraction, are: for Fe between 0.97277% - 4,11822% , for Mn between 0.022437% - 0.501866%, and for Ni between 0,0009714% - 0.03034%.